2016
DOI: 10.19072/ijet.05966
|View full text |Cite
|
Sign up to set email alerts
|

Study on Machining Parameters for Thrust Force and Torque in Milling AA7039 Composites Reinforced with Al2O3/B4C/SiC Particles

Abstract: Abstract-Metal matrix composites are used in many industrial fields such as automobile, military and aerospace applications due to their superior mechanical properties. In the present study, three aluminum 7039 metal matrix composite (MMCs) samples reinforced with 10 wt.% particulates of aluminum oxide (Al 2 O 3 ), 10 wt.% boron carbide (B 4 C), and 10 wt.% silicon carbide (SiC) were successfully fabricated using a powder metallurgy and hot extrusion method. The influences of cutting parameters on the thrust c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The spindle speed did not show any significant impact on the thrust force; however, as the spindle speed increased only a slight decrease or at high feeds, a slight increase was observed. The slight decreased in the thrust force due to an increase in spindle speed was due to an increase in the cutting temperature which affected the strength of the workpiece in the plastic deformation region and thus, cutting forces decreased [40]. According to Zhang et al [41], during the drilling process, most of the heat in the plastic deformation zone and the surrounding regions at the interfaces between the tool, workpiece and chip caused the high temperature.…”
Section: Thrust Forcementioning
confidence: 99%
“…The spindle speed did not show any significant impact on the thrust force; however, as the spindle speed increased only a slight decrease or at high feeds, a slight increase was observed. The slight decreased in the thrust force due to an increase in spindle speed was due to an increase in the cutting temperature which affected the strength of the workpiece in the plastic deformation region and thus, cutting forces decreased [40]. According to Zhang et al [41], during the drilling process, most of the heat in the plastic deformation zone and the surrounding regions at the interfaces between the tool, workpiece and chip caused the high temperature.…”
Section: Thrust Forcementioning
confidence: 99%
“…2020, 10, x FOR PEER REVIEW 5 of 20 spindle speed. According to Karabulut [41], the increase in temperature at high spindle speed affects the strength of the workpiece and causes the plastic deformation of the workpiece, which leads to a reduction in thrust force. Further, at the highest spindle speed selected in this study, a slight increase in the thrust force was observed at the high feed, which might be due to the increase in the number of holes, which promotes tool wear due to high friction at the interface of the tool-workpiece and subsequent high-force generation [42].…”
Section: Analysis Of Thrust Forcementioning
confidence: 99%
“…Tis reduction can be attributed to the heat generated in the penetration area of the drilled hole, which lowers the material's hardness and, hence, results in a lower Fz [48]. Additionally, the Fz decreases due to increased material ductility caused by n drilling temperature [49,50]. Figure 7 demonstrates that a rise in f from 0.12 to 0.3 mm/rev leads to rise in Fz.…”
Section: Trust Forcementioning
confidence: 99%